The Practice of Living the Qur'an as a Media for Internalizing the Values of Surah Yasin in Forming the Religious Character of Students at SMP it Nurul Fadhilah - Balqis Mawadda; Agusman Damanik (Mukaddimah: Jurnal Studi Islam, 2026)
The formation of students' religious character in the modern era faces various challenges due to the suboptimal internalization of religious values ​​in daily life. In many educational institutions, the habit of reading the Qur'an is still viewed as a religious routine, so it has not been widely studied as a Living Qur'an practice that can connect the Qur'an text with the formation of students' character. This study aims to analyze the practice of Living Qur'an as a medium for internalizing the values ​​of Surah Yasin in the formation of students' religious character at SMP IT Nurul Fadhilah. The study employed a qualitative approach with fieldwork. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the practice of Living the Qur'an is realized through the habit of reciting Surah Yasin every Friday morning, combined with the memorization and tahsin programs. The tradition of repeating Surah Yasin verse 82 three times shows the performative, hermeneutic, and functional reception of the Al-Qur'an so that this practice not only becomes a ritual activity but also becomes a medium for internalizing the values ​​of monotheism, trust, prayer, and love for the Al-Qur'an. This process encourages changes in students' attitudes from obedience to school rules to religious awareness, which is reflected in the discipline of worship, respect for parents and teachers, responsibility, and the habit of interacting with the Koran outside the school environment. This Research contributes to the development of Living Qur'an studies in the context of Islamic education by showing that the practice of Living Qur'an can function as a medium for internalizing Al-Qur'an values ​​in the formation of students' religious character. Keywords: Internalization of Values, Surah Yasin, Religious Character, Living Qur'an.